2023
DOI: 10.20961/lar.v21i1.66998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of primers targeting chromo helicase DNA-binding gene (CHD) for molecular sexing identification in four bird families

Abstract: <p><span class="fontstyle0">Objective: </span></p><p><span class="fontstyle2">Sex determination of birds is crucial role in breeding and conservation purposes. Genomic approaches by using basis of bird sex polymorphism are accepted to generate an accurate sexing procedure. The PCR method is commonly used and known to provide accurate test results in determining the sex of birds, but its successes is strongly influenced by the compatibility of the primers used with the DNA te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Those conventional methods above tend to have weaknesses, such as requiring a long time, experience, special expertise and invasive (Volodin et al, 2015;Purwaningrum et al, 2019;Elnomrosy et al, 2022). Disastra (2021) and Fitriana et al (2023) has been demonstrated the error of bird sellers in determining sexes in various families, based on external morphological observations.…”
Section: Introductionmentioning
confidence: 99%
“…Those conventional methods above tend to have weaknesses, such as requiring a long time, experience, special expertise and invasive (Volodin et al, 2015;Purwaningrum et al, 2019;Elnomrosy et al, 2022). Disastra (2021) and Fitriana et al (2023) has been demonstrated the error of bird sellers in determining sexes in various families, based on external morphological observations.…”
Section: Introductionmentioning
confidence: 99%